Tigers in trouble : financial governance, liberalisation and crises in East Asia edited by Jomo K.S.. - Jomo K. S. (Hong Kong University Press: IPSR Books: University Press: Zed Books: Distributed in the USA exclusively by St. Martin's Press, 1998)
"This book provides a cogent critique of the nature of Southeast Asian capitalism. It argues powerfully that the crises are due not to excessive regulation, but to too much financial liberalisation and a consequent undermining of monetary and fiscal governance. While recognising some macroeconomic problems and abuses of state intervention in the region, the book also highlights the nature and implications of IMF and domestic policy responses which exacerbated the crises." "The analysis contained in this book raises profound questions which resonate way beyond the Asian region itself. They relate to the appropriate role of the state, the policies of the IMF and the viability of the deregulated free market capitalist model which these and other Third World countries have been encouraged to pursue."--Jacket.